Exploring the Epidemiological Characteristics and Survival Analysis Among Prostate Cancer Patients Under 50: A Seer‐Based Population Study - Bahaa Mali; Ali Mali; Alaa Mali; Mohammed Abdulrazzak; Afnan W. M. Jobran (Health Science Reports)
ABSTRACT Background and Aims Even though aging is a known risk factor for prostate cancer incidence and mortality, there has been an increase in incidence among young men since the late 1980s with notably lower survival rates than those among older men. However, there is insufficient knowledge about recent trends in the incidence and survival of this disease. Methods We analyzed prostatic cancer incidence trends in men under 50 from 1975 to 2020 using Surveillance, Epidemiology, and End Results (SEER) 8 registries data. We further studied frequency, incidence rate, and survival rates in this group across SEER 22 registries, which cover around 41.9% of the US population. We analyzed the data by age, stage, and race subgroups and identified potential risk factors affecting survival prognosis using multivariable Cox proportional hazards regression models. Results Our results revealed that prostate cancer incidence rates in men under 50 have increased from 1975 to 2020. There was a significant decline from 2009 to 2014, followed by a gradual decrease. Between 2004 and 2020, 35,670 new cases were diagnosed. 76.10% of these cases were localized, 15.10% were regional, 4.20% were distant, and 4.60% were unstaged. Certain factors can negatively impact the prognosis, including age at diagnosis under 30, advanced stages of the disease, and non‐Hispanic black race. Conclusion Early‐onset prostate cancer has distinct epidemiological and clinical characteristics, and more research is required to gain a better understanding of the biological, genetic, and environmental factors that contribute to its development. This understanding will assist in the creation of more suitable management plans that can enhance survival rates.